A qualitative study of Norwegian first-time mothers' information needs in pre-admission early labour. (September 2021) - Myhre, Enid Leren; Lukasse, Mirjam; Reigstad, Marte Myhre; Holmstedt, Viggo; Dahl, Bente
Highlights: Women required information as soon as they entered early labour. Women wanted trustworthy online information from reliable sources in early labour. No matter how prepared women felt, unexpected situations occurred in early labour. Abstract: Objective: To explore women's experience with information, and their information needs in pre-admission early labour. Design: A qualitative study with an exploratory and descriptive approach. Setting: Five focus group interviews with women attending post-natal care at five different well-baby clinics in South-Eastern Norway in 2019. Participants: Sixteen first-time mothers who had given birth to a baby 3–17 weeks prior to the focus group interview. All had experience of staying at home in early labour. Findings: Three themes emerged from the analysis. The first and most substantial theme involved information. The women considered it necessary to have easy access to a suitable amount of trustworthy information at the appropriate time. The second theme described that the women were surprised at how early labour manifested, despite having prepared for it. The third theme was about receiving acknowledgement and support, revealing that information did not meet all woman's needs. Key conclusions and implications for practice: The women found it challenging to prepare for early labour, and no matter how prepared they felt beforehand, unexpected situations arose. Easily accessed online information from reliable sources was useful in early labour, but in order for women to feel safe at home, this should be complemented by telephone conversations with skilled and welcoming midwives in the labour ward. More knowledge about women's information needs in early labour is required, including studies exploring how the information should be provided to help women feel safe when staying at home in early labour.